2021
DOI: 10.1016/j.isci.2020.101937
|View full text |Cite
|
Sign up to set email alerts
|

Circulating argonaute-bound microRNA-126 reports vascular dysfunction and treatment response in acute and chronic kidney disease

Abstract: Summary Vascular and kidney dysfunction commonly co-exist. There is a need for biomarkers of vascular health. Circulating microRNAs are biomarkers; miR-126 is endothelial cell-enriched. We measured circulating miR-126 in rats with nephrotoxic nephritis (NTN) and humans with acute endothelial and renal injury (vasculitis associated with autoantibodies to neutrophil cytoplasm antigens (ANCAs)). We compared these findings to those from patients with chronic kidney disease (CKD) and end-stage renal dise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Moreover, miRNAs participate in cellular process, including the growth of renal tubular epithelial cells ( 13 , 14 ). Meanwhile, miRNAs have been reported to be associated with AKI progression ( 15 17 ). For instance, miR-21 has been shown to inhibit the progression of AKI ( 18 ); Jiang et al ( 19 ) found that miR-500a-3p alleviated kidney injury by targeting mixed lineage kinase domain like pseudokinase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs participate in cellular process, including the growth of renal tubular epithelial cells ( 13 , 14 ). Meanwhile, miRNAs have been reported to be associated with AKI progression ( 15 17 ). For instance, miR-21 has been shown to inhibit the progression of AKI ( 18 ); Jiang et al ( 19 ) found that miR-500a-3p alleviated kidney injury by targeting mixed lineage kinase domain like pseudokinase.…”
Section: Introductionmentioning
confidence: 99%
“…This information did not, however, exclude a potential role of miR-126 in the pathophysiology of CKD, thus we wanted to further explore this hypothesis in the present follow-up study. In support of this, Scullion et al recently showed that miR-126 serum was reduced in rats with nephrotoxic nephritis and in humans with both acute endothelial and renal injury compared to healthy controls [ 11 ]. Furthermore, in this work, miR-126 increased dramatically post-treatment but remained lower than in healthy animals.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we have described a clear link between miR-126 and vascular injury in CKD models [ 7 , 8 , 23 ], as well as a decrease in the serum levels of this miRNA in CKD patients [ 6 ]. In addition, Scullion et al found a strong correlation between (1) circulating miR-126 and (2) pulse-wave velocity and Asymmetric Dimethylarginine (ADMA), both markers of endothelial function [ 11 ]. Our novel results strengthen the hypothesis of a link between miR-126 levels and endothelial dysfunction in a large cohort of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend was observed in a study looking at circulating miR-126 decrease as a biomarker for vascular dysfunction. Whilst large variation was seen in healthy and patient cohorts, miR-126 remained 88-fold lower in vasculitis patients than controls, suggesting its use as a potential vascular injury marker (Scullion et al 2021).…”
Section: Inter-and Intra-individual Variability In Basal Mir Expressionmentioning
confidence: 99%